SUBJECT, TASKS AND PRINCIPLES OF LEGAL PSYCHOLOGY (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Features of the development of psychological knowledge depend not only on the connections between psychology and other sciences. They are no less determined by the growing needs of social practice. As is known, previously psychology was predominantly a theoretical (worldview) discipline, but now, while maintaining its cognitive role, it is increasingly becoming an area of ​​professional practical activity in industry, public administration, the education system, healthcare, culture, sports, etc.Thus, modern psychology is a very extensive system of scientific disciplines, at different stages of formation and associated with various areas of practice.